Systematic review: Comparison of halal regulations in Asia - Fadhillah, Azzam Akbar; Saputra, Reza (Journal of Halal Science and Research, 2025)
The harmonization of halal standards in Asia is crucial for boosting regional trade, ensuring consumer confidence, and meeting religious requirements in the growing halal industry. This systematic review employed a qualitative comparative analysis of 9 key journal articles and 8 major halal regulations in Asia, including Malaysia's MS 1500-2009, OIC/SMIIC 1:2019, Saudi Arabia's SASO 2172, and UAE.S 2055-1:2015, as well as recent changes in Indonesia's laws (Law No. 33/2014, Law No. 6/2023, PP No. 39/2021, and PP No. 42/2024). This analysis reveals significant differences in halal definitions, certification protocols, and the role of regulatory authorities, which hinder harmonization. Specifically, it was found that countries such as Indonesia, Malaysia, Saudi Arabia, and Brunei implement mandatory halal policies, while others like Japan, Thailand, and India adopt voluntary approaches. The review highlights that while countries share common goals of food safety and sharia compliance, cultural and technological variations, alongside certification costs for MSMEs, remain significant barriers. Mutual recognition agreements, cross-border compliance, and the adoption of technologies like blockchain are emphasized as essential for fostering transparency and an integrated halal market. This study provides fresh insights into the benefits of harmonizing halal standards for producers, consumers, and regulators, ultimately aiming to reduce trade barriers, increase trust, and support regional economic growth. Keywords: Asia halal certification, Asia trade, Blockchain technology, Halal standard, Regional harmonization.